Japan Unified Protocol Clinical Trial for Depressive and Anxiety Disorders (JUNP study): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Ito, Masaya; Okumura, Yasuyuki; Horikoshi, Masaru; Kato, Noriko; Oe, Yuki; Miyamae, Mitsuhiro; Hirabayashi, Naotsugu; Kanie, Ayako; Nakagawa, Atsuo; Ono, Yutaka
Abstract Background The unified protocol for the transdiagnostic treatment of emotional disorders is a promising treatment approach that could be applicable to a broad range of mental disorders, including depressive, anxiety, trauma-related, and obsessive-compulsive disorders. However, no randomized controlled trial has been conducted to verify the efficacy of the unified protocol on the heterogeneous clinical population with depressive and anxiety disorders. Methods/design The trial was designed as a single-center, assessor-blinded, randomized, 20-week, parallel-group superiority study in order to compare the efficacy of the combination of unified protocol and treatment-as-usual versus waiting-list with treatment-as-usual for patients with depressive and/or anxiety disorders. The primary outcome was depression at 21 weeks, assessed by the 17-item version of the GRID-Hamilton Rating Scale for Depression. Estimated minimum sample size was 27 participants in each group. We will also examine the treatment mechanisms, treatment processes, and neuropsychological correlates. Discussion The results of this study will clarify the efficacy of the unified protocol for depressive and anxiety disorders, and the treatment mechanism, process, and neurological correlates for the effectiveness of the unified protocol. If its efficacy can be confirmed, the unified protocol may be of high clinical value for Japan, a country in which cognitive behavioral treatment has not yet been widely adopted. Trial Registration ClinicalTrials.govNCT02003261 (registered on December 2, 2013)